Oxidation Products for Methyl Ethyl Sulfide CH3SCH2CH3 under Standard Conditions- A Thermodynamic Study - Hebah Abdel-Wahab; Tamara Gund (Current Topics on Chemistry and Biochemistry Vol. 3, 2022)
Methyl ethyl sulfides are used in organic synthesis and scientific research. Significant amount of ethyl methyl sulfide is emitted to the atmosphere due to biological activity in the sea, and the concentration of ethyl methyl sulfide is result of anthropogenic and human activity. Methyl ethyl sulfides has a negative effect on the atmosphere as it produces sulfuric oxides in the environment. The study of methyl ethyl sulfide oxidation products is of value to know the fate of its oxidation products in the atmosphere. The objective of this work is to find the products of oxidation of methyl ethyl sulfide under standard conditions and at different temperature using thermodynamic data. For all conceivable reaction paths of oxidation of radicals of methyl ethyl sulfide radicals, entropy and Gibb’s free energy change were computed. The enthalpy change for the chemical pathways was computed as well, and the results were compared to those obtained using the CBS-QB3 DFT approach. It has been found that the energetically favorable stable products formed from oxidation of ethyl methyl sulfide at standard conditions, 298 K and 1 atm pressure are acetaldehyde (CH3CH=O), thioformaldehyde (CH2=S), thio-acetaldehyde (CH3CH=S), and formaldehyde (CH2=O).